The Influence of Leadership Style and Employee Engagement on Employee Performance of PT Maybank Deltamas Branch - Marhamah Izat Rodliyah; Nur Asni Gani (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The objectives of this study are as follows: (1) To determine the effect of leadership style on employee engagement. (2) To determine the effect of leadership style on employee performance. (3) To determine the effect of employee performance on employee engagement. (4) To determine the effect of leadership style and employee engagement on employee performance. The research uses observation and questionnaire methods as instruments. The respondents were 35 employees from the Deltamas, Grand Wijaya, and Fatmawati branches. The sampling process uses a probability sampling technique and a quantitative approach. The result shows that leadership style has an insignificant effect on employee performance with the value of the t count and t table smaller than the t table (-348 2.036). Employee engagement has a positive and significant effect on employee performance with t count and t table greater than t table (5.922 > 2.036).